Binocular head-mounted chromatic pupillometry can detect structural and functional loss in glaucoma - Quan, Yadan; Duan, Huiyu; Zhan, Zongyi; Shen, Yuening; Lin, Rui; Liu, Tingting; Zhang, Ting; Wu, Jihong; Huang, Jing; Zhai, Guangtao; Song, Xuefei; Zhou, Yixiong; et al. (Frontiers in Neuroscience, 2023)
Aim The aim of this study is to evaluate the utility of binocular chromatic pupillometry in detecting impaired pupillary light response (PLR) in patients with primary open-angle glaucoma (POAG) and to assess the feasibility of using binocular chromatic pupillometer in opportunistic POAG diagnosis in community-based or telemedicine-based services. Methods In this prospective, cross-sectional study, 74 patients with POAG and 23 healthy controls were enrolled. All participants underwent comprehensive ophthalmologic examinations including optical coherence tomography (OCT) and standard automated perimetry (SAP). The PLR tests included sequential tests of full-field chromatic stimuli weighted by rods, intrinsically photosensitive retinal ganglion cells (ipRGCs), and cones (Experiment 1), as well as alternating chromatic light flash-induced relative afferent pupillary defect (RAPD) test (Experiment 2). In Experiment 1, the constricting amplitude, velocity, and time to maximum constriction/dilation were calculated in three cell type-weighted responses, and the post-illumination response of ipRGC-weighted response was evaluated. In Experiment 2, infrared pupillary asymmetry (IPA) amplitude and anisocoria duration induced by intermittent blue or red light flashes were calculated. Results In Experiment 1, the PLR of POAG patients was significantly reduced in all conditions, reflecting the defect in photoreception through rods, cones, and ipRGCs. The variable with the highest area under the receiver operating characteristic curve (AUC) was time to max dilation under ipRGC-weighted stimulus, followed by the constriction amplitude under cone-weighted stimulus and the constriction amplitude response to ipRGC-weighted stimuli. The impaired PLR features were associated with greater visual field loss, thinner retinal nerve fiber layer (RNFL) thickness, and cupping of the optic disk. In Experiment 2, IPA and anisocoria duration induced by intermittent blue or red light flashes were significantly greater in participants with POAG than in controls. IPA and anisocoria duration had good diagnostic value, correlating with the inter-eye asymmetry of visual field loss. Conclusion We demonstrate that binocular chromatic pupillometry could potentially serve as an objective clinical tool for opportunistic glaucoma diagnosis in community-based or telemedicine-based services. Binocular chromatic pupillometry allows an accurate, objective, and rapid assessment of retinal structural impairment and functional loss in glaucomatous eyes of different severity levels.